Wuhan - Murphy, Larissa (Te Kaharoa, 2020)
Watered down vinyl detergent fills my room from the halls every morning. My eyes force themselves open; there is always a millisecond of hope that my waking life is a dream. It’s always grey here. There’s no clock in here; just a calendar, perhaps to count the days of my abandonment. Oh, how much I would give to have my own bathroom again. Long grey strands of hair hang dead along my face as I take small tired steps, shuffling towards the communal bathroom. Nanny Pa warned me how fast our whānau age. I refused to believe him. Loose skin flapping as I walk, and hard for me to ignore. I try to console myself; my skin reflects my story. Rays of morning sun weave through the hall and warm my delicate skin. I wish my room would get some light. I tilt my head, “stir it up, little darling, stir it up...” echoes through the hall speakers. I pause and feel my heart flutter.